Penerapan Terapi Kompres Air Hangat Terhadap Nyeri Dismenore Pada Remaja di Desa Pilangrejo Boyolali - Maya Melinda Oktaviani; Exda Hanung Lidiana (STIKes Ibnu Sina Ajibarang, 2023)
Background: Dysmenorrhea is pain experienced by adolescents during menstruation in the lower abdomen due to changes in the hormone prostaglandin. Based on the interviews conducted, 10 out of 67 young women experienced dysmenorrhea in Pilangrejo Village. Warm water compresses are a non-pharmacological treatment because they are effective in helping reduce dysmenorrhea pain. Objective: To find out the results of implementing warm water compress therapy for dysmenorrhea pain. Method: This application uses the case study method with 2 respondents in Cungkup, Pilangrejo, Juwangi, Boyolali who experienced primary dysmenorrhea with a moderate pain scale. Each respondent was given warm water compresses for 3 consecutive days with a duration of 20 minutes and a water temperature of 46°C. Result: The management of dysmenorrhea in adolescents with warm water compresses decreased in the first respondent from a pain scale of 6 to 2 with the moderate to mild pain category, and the second respondent experienced a decrease in the pain scale from 5 to 1 with the moderate to mild pain category. Conclusion: There is a difference in the pain scale of dysmenorrhea in the 2 respondents before and after being treated with warm water compresses with a moderate pain scale to mild pain.